Influence of connection type (internal VS. external) on implant impression accuracy: an in vitro study - Ventura, Rita de Cássia Cabral (2017)
Tese de Mestrado, Medicina Dentária, Universidade de Lisboa, Faculdade de Medicina Dentária, 2015